Information security and information hygiene on internet media - Varynskyi, Vladyslav; Varynska, Alla; Kostytsky, Mychailo; Kushakova-Kostytska, Nataliia (Nexo Revista Científica, 2021)
The relevance of the problem of ensuring information security at the level of “information hygiene” is due to the risks of the negative potential of Internet media. The purpose of the article is to analyse the state of the hygiene segment of the information security of Ukrainian Internet media under global threats. The leading research method for this problem is content analysis, which allows to determine the qualitative features of modern media information based on psycholinguistic markers of information. It has been established that the largest part in the information space of Internet media is fake information, and therefore special attention is paid to its analysis. The article highlights the main markers by which you can determine the fake. The need for critical familiarization with the information is noted. The results of the study expand the understanding of the concepts of information security and information hygiene.